Bacteriological profile, antibiotic sensitivity pattern, and detection of extended?spectrum ?-lactamase in the isolates of urinary tract infection from children - Shettigar, Sanchita; Chandrashekar, G S; Roche, Ronald; Nayak, Narendra; Anitha, K B; Soans, Santhosh (Indian Journal of Child Health, 2016)
Background: Appropriate use of antibiotic in children with urinary tract infection (UTI) is essential so as to curb the spread of drug-resistant organisms. Objectives: To study the bacteriological profile and antibiotic sensitivity pattern in children with UTI and to determine the prevalence of extended-spectrum ?-lactamase (ESBL) producers of Escherichia coli and Klebsiella species. Methods: This prospective study was conducted from October 2010 to September 2011. The children between age group of 3 and 14 years who attended Pediatric Department at a tertiary care hospital were included in the study. Single midstream urine specimen was collected from each patient with suspected UTI. Result: Out of 184 urine samples with suspected UTI, 122 children had culture-proven UTI. Of 122 cases, 81 (66.39%) cases were seen in females. The most common organism isolated was E. coli (50%) followed by Klebsiella pneumoniae (23.77%) and Enterococcus species (8.19%). E. coli, Klebsiella spp., Citrobacter freundii, and Proteus mirabilis responded better to nitrofurantoin (NIT) (76.8%). Ceftriaxone (79.12%), cefotaxime (74.8%), and cefixime (71.7%) showed higher sensitivity as compared to ceftazidime (63.4%) and cefoperazone (CPZ) (59.4%). Among aminoglycosides, amikacin (82.4%) had a better response as compared to gentamicin (64.6%). Out of 61 E. coli and 31 Klebsiella species, 35 (38.04%) were ESBL producers. The sensitivity of these organisms to imipenem was 100% with a good response to meropenem, CPZ-sulbactam, and piperacillin-tazobactam. Conclusion: E. coli and Klebsiella spp. were the most common isolates and many of them were ESBL producers. NIT seemed to be a reasonable alternative to cephalosporins for the treatment of UTIs in children. Carbapenems were found to be effective in ESBLs and non-ESBL producing uropathogens and can be considered as reserve drugs.